Supporting students in practice part 1: clinical supervisor role. (2nd October 2022) - Holt, Susan L; Vivian, Sarah; Hooper, Susan
Abstract : The clinical learning environment is a complex sociocultural landscape. It can be a challenging place to manage in a way that appropriately supports the professional development of student veterinary nurses (SVNs). One of the most influential factors in determining student satisfaction in this environment is the role played by the clinical supervisor. Clinical supervisors who are proactive in their role can provide a sense of belonging in the induction phase, function as positive professional role models and support timely progress through regularly planned training and tutorials. There are also benefits for the clinical supervisor, such as an increased sense of job satisfaction and maintaining up-to-date clinical knowledge.